His Acts, Her Words: The male and feminine characters in Eric Rohmer’s films - Ferencuhova, Maria (Sens public)

(untitled) (Département des littératures de langue française, 2008)
For a standard study of gender differences in the characters of modern cinema, the most evident possibility might be to examine the transformation of the typical heroes of the two most popular cinematic genres, that’s to say, in melodrama and action films. Choosing this course of action, however, would most certainly lead to a more or less rough generalization that, rather than reporting the progress of change in the cinematographic models of what we can call “a heroine” or “a hero,” would rather be just another contribution to the stereotyped images of contemporary women and men. It is for this reason that I chose – so as to show the inevitable differentiation of the two sexes - a cinematic concept that is completely different, that of Eric Rohmer. In his films, the representation of man and woman is not defined as the « politically correct » concept of the two sexes (that which has recently been very popular, especially in American cinema.) For Rohmer, rather, gender difference pertains to a repressed or barely discernable representation of masculine and feminine stereotypes, equally as far as discussion is concerned as is action, two of the most important elements in this director’s films.